2018
DOI: 10.1103/physrevlett.121.145503
|View full text |Cite
|
Sign up to set email alerts
|

Higher Temperatures Yield Smaller Grains in a Thermally Stable Phase-Transforming Nanocrystalline Alloy

Abstract: Grains in crystalline materials usually grow with increased thermal exposure. Classical phenomena such as recrystallization may lead to a purely temporary decrease in the grain size, while recent advances in alloy design can yield thermally stable nanocrystalline materials in which grain growth stagnates. But grains never shrink, since there is a lack of interfacegenerating mechanisms at high temperatures, which are required to decrease the grain size if such was the system's thermodynamic tendency. Here we si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 50 publications
0
5
0
2
Order By: Relevance
“…It was recently suggested that polycrystalline materials could approach their thermodynamically stable (equilibrium) state following two different routes, namely “from below” and “from above” [ 62 ]. Specifically, the equilibrium grain size can be eventually attained starting from materials characterized by “finer” or “coarser” structures (cf.…”
Section: Methodsmentioning
confidence: 99%
“…It was recently suggested that polycrystalline materials could approach their thermodynamically stable (equilibrium) state following two different routes, namely “from below” and “from above” [ 62 ]. Specifically, the equilibrium grain size can be eventually attained starting from materials characterized by “finer” or “coarser” structures (cf.…”
Section: Methodsmentioning
confidence: 99%
“…segregation-desegregation transition at the grain boundaries. 108 Such remarkable effects are caused by the unique competition between phases and complexions that can occur in the "closed system" of a nanocrystalline structure with a high-volume fraction of grain-boundary sites.…”
Section: Grain-boundary Alloying: Intentional Segregationmentioning
confidence: 99%
“…Отметим, что изменение структуры наночастиц при уменьшении их размера было экспериментально обнаружено для многих однокомпонентных веществ и сплавов [33][34][35][36]. Например, в [33] было обнаружено, что при уменьшении размера наночастицы железа структура в ней изменяется из ОЦК-на ГЦК-структуру, которая стабильна для макрожелеза только при высоких температурах.…”
Section: изменение параметров гцк-оцк фазового перехода при уменьшении размера наночастицы сплава Au-feunclassified
“…В [34] было экспериментально показано, что наночастицы сплава Au-Fe меньше определенного размера уже не испытывают структурный фазовый переход в ОЦК-фазу. В [35] было экспериментально показано, что для сплава Au-Fe, подвергнутому ГЦК-ОЦК-переходу, высокотемпературная ГЦК-фаза имеет стабильный мелкий размер, меньший, чем ее низкотемпературная ОЦК-фаза. В обзоре [36] указаны экспериментальные работы, в которых были получены наночастицы Au, имеющие стабильные кристаллические структуры, которые были отличны от ГЦК-структуры.…”
Section: изменение параметров гцк-оцк фазового перехода при уменьшении размера наночастицы сплава Au-feunclassified